Research on opportunities of operation of speed passenger trains by the couple unit system on the railway of ukraine (Transport systems and technologies, 2019)
In the work investigated the direction of introduction of technology for the organization of multiply-units speed trains, which will reduce the cost of developing variable demand of train routes, and improve the quality of passenger service. In order to increase the efficiency of transportation in high-speed trains, it is necessary to use organizational technologies, which are based on concepts, that meet the requirements of the variable basis of the organization of passenger transportation and allow to provide a flexibility for companies-carriers. Was analyzed experience of operating high-speed electric trains on multiply-units control system. The modular operation of high-speed trains offers the ability to combine trains into two or even three trains with the possibility of adapting to changing time and space requirements. This makes it possible to use short-haul trains, which can be combined with trains of higher complexity to meet variable demand on railway network. In the work we find a solution for the problem of constructing a plan for the formation of connected high-speed trains on the network graph, and proposed an improved model of the current variant of the Intercity+ high-speed train on the Kiev-Przemysl route using connecting two high-speed trains.
Keywords: rail, high-speed trains, Intercity , multiply-units control system, modeling